Survey of wireless sensor network security techniques - PEI Qing-qi1; SHEN Yu-long1; MA Jian-feng1 (Tongxin xuebao)
The current situations of sensor network security,the security challenges and the security problems were pre-sented.From the aspects of key management,secure routing,authentication,intrusion detection,DoS attack,access con-trol,all the security techniques of sensor networks were introduced and discussed,and the comparisons were made to help researchers select and design the security solutions for a particular sensor network application environment.At last,the further direction of sensor network security techniques was summarized and discussed.